Experimental and numerical analysis of nanoindentation of Ti-6246 alloy. (19th May 2018) - Khan, Muhammad Irfan; Shakoor, Abdul; Azam, Khizar; Habib, Muddasar; Muhammad, Riaz; Shah, Shoukat Ali; Khan, Afzal
ABSTRACT: Titanium and its alloys exhibit a very desirable set of mechanical properties like high strength-to-density ratio, high corrosion resistance, and the ability to work safely in extreme temperature conditions. In this work, nanoindentation technique was used to evaluate the mechanical properties of Ti-6246 alloy. The response of material to the indentation load was checked with light microscopy, and scanning electron microscopy (SEM) imaging was done to study the area around the indents for any sinks-in or piles-up. The light microscopy and SEM images are presented in this work and discussed in detail. In this work it was found that nanoindentation can be successfully used to evaluate the mechanical properties of high-strength material like Ti-6246. The hardness values and Young's modulus values obtained in this work were found to be in close agreement to that reported in literature. A finite-element model was developed for the nanoindentation processes of the studied alloy using commercially available finite-element software DEFORM 3D. The model was used for parametric analysis of the nanoindentation process, and results obtained from FEA model were in good agreement with the experimental results.